Π‐Conjugated Molecule Boosts Metal–Organic Frameworks as Efficient Oxygen Evolution Reaction Catalysts. Issue 50 (16th October 2018) - Zhu, Rongmei; Ding, Jiawei; Xu, Yuxia; Yang, Jinpeng; Xu, Qiang; Pang, Huan
Abstract: To improve the efficiency of water electrolysis, developing efficient oxygen evolution reaction (OER) electrocatalysis is extremely important due to its four‐electron transfer dynamics. In this work, a π‐conjugated molecule (2, 3, 6, 7, 10, 11‐hexahydroxytriphenylene, HHTP), which can accelerate the electron transfer, is coated directly on pristine ZIF‐67, resulting in a composite named HHTP@ZIF‐67, via a simple one‐step solvothermal method. The obtained HHTP@ZIF‐67 possesses a Brunauer–Emmett–Teller surface area of 2013.9 m 2 g −1 and displays microporous behavior, which can provide enough active sites for OER. The double‐layer capacitance of HHTP@ZIF‐67 is also enhanced, corresponding to an enlarged electrochemical active surface area. HHTP@ZIF‐67 presents a quite low overpotential of 238 mV at 10 mA cm −2 in 1.0m KOH. This material synthesized via the simple coating strategy is promising in the application of energy conversion devices. Abstract : A novel metal–organic framework (MOF) composite 2, 3, 6, 7, 10, 11‐hexahydroxytriphenylene@ZIF‐67 is obtained via a direct coating strategy under solvothermal conditions. The conductivity of the obtained composite is extremely ameliorated due to the improved electron transfer resulting from the π‐conjugated skeleton. Together with the high specific surface area preserved from the pristine MOFs, the synthesized composite displays efficient electrocatalytic activity in the oxygen evolution reaction performance.